OCCUPATIONAL INJURIES IN WELDERS - RESULTS FROM A SIX MONTH FOLLOW-UP STUDY - Shaikh, Masood Ali; Shaikh, Irshad Ali (Journal of Ayub Medical College Abbottabad, 2005)
Background: Injuries are an under recognized public health problem globally. We assessed the number and type of occupational injuries in welders, in a prospective manner. Methods: A cohort of 208 welders was re-interviewed twice at three-month intervals to determine the type and frequency of injuries in the welders primarily involved in the automobile sector, in the twin cities of Islamabad and Rawalpindi in Pakistan. Data was analyzed for frequencies and counts with STATA 8. Results: Cumulatively, 105 injuries were reported by 61 welders in the two follow-ups, who took 28 days off as a result of these injuries, in the past six months. Four welders reported multiple injuries involving the same injury episode. None of the welders reported any permanent disfigurement as a result of these injuries. Conclusion: Occupational injuries are common in the welders working primarily in the automobile sector in the twin cities of Islamabad and Rawalpindi. Foreign bodies in the eyes are the most common type of injuries sustained by these welders. Key Words: Injuries, Welders, Pakistan